Decomposition of Empty Fruit Bunch and its Interaction with Inorganic N and K Fertilisers in Oil Palm - Lim, Kim Chiew (1998)
Investigations to study the multifactorial interactions between applying varying rates (M) of empty fruit bunch (EFB) with different rates of inorganic nitrogen (N) and potassium (K) fertilisers and to determine the effects of these inorganic fertilisers on decomposition and mineralisation rates of EFB in mature oil palm were undertaken. Two experiments were carried out viz. EFB-nutrient interaction studies and EFB decomposition and nutrient mineralisation studies. Significant M x N interactions were detected in all palm growth parameters and some important soil chemical properties. Palm nutrition, vegetative vigor and yield of fresh fruit bunch (FFB) were all enhanced, with the exception of leaf magnesium levels which significantly decreased. Significant M x K interaction enhanced leaf potassium level but decreased leaf magnesium. No significant effects on leaf nitrogen and phoshorus were detected. Vegetative vigor and yield were also significantly increased but no M x K significant effects were detected on soil chemical properties. There was a rapid initial dry matter loss of the EFB with declining rates at the later months after field application. Total physical disintegration was observed at eight months with dry matter loss of 70%, after which there was hardly any loss up to the 10th month. Differences in decomposition rates were detected among the three layers of EFB. Inorganic N additions generally increased EFB decomposition